Rancang Bangun Sistem Informasi Perpustakaan Berbasis Web untuk Meningkatkan Efisiensi Pengelolaan Data dan Kemudahan Akses Informasi pada SMK Islamiyah Ciputat - Hisyam Santoso; Dewi Intan Mayangsari; Rio Adiguna; Maulana Ardhiansyah (CV. Shofanah Media Berkah, 2026)
School libraries play a vital role in supporting teaching and learning activities; however, library management at SMK Islamiyah Ciputat is still carried out manually using ledgers. This situation makes the process of recording book data, member information, loans, returns, and report generation less effective and prone to recording errors and data loss. Furthermore, the lack of a digital catalog makes it difficult for students and teachers to quickly obtain information about book availability. This study aims to design and develop a web-based library information system at SMK Islamiyah Ciputat to improve the efficiency of data management and access to library information. The developed system features book data management, user management, a digital catalog, borrowing and return transactions, and library reports. The results of the implementation show that the web-based library information system can help library staff manage data in a more structured manner, reduce reliance on manual record-keeping, speed up the information search process, and make it easier for students and teachers to check the availability of books in the collection. Black-box testing shows that the system’s main functions operate in accordance with user needs.